2018
DOI: 10.18805/ijare.a-308
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the hybrid seedling performance of forage sorghum and silage corn under Jordan irrigation conditions

Abstract: The beta casein gene (CSNS2) has 12 genetic variants divided into two groups: the first group (A1, B, and G) which differ from the second group (A2, A3 C, D, E, F, H, H2 and I) where A base replaces C base, this leads to potential liberation of a bioactive peptide, b-casomorphin, upon digestion where a histidine replaces a proline at position 67. The allele specific polymerase chain reaction (AS-PCR) was evaluated to distinguish between the beta casomorphin releasing variants (A1 and B) and the non-releasing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Climate change indicated that the productivity of forage crops is highly variable in simulated extreme drought conditions of Jordan, where rainfall or irrigation amounts and distribution are highly variable. [13] reported that selection of specific drought-tolerant hybrid of silage corn seeds in Jordan would be an efficient and useful method of improving uniformity, water use efficiency, and providing superior seedling performance with the potential for improved vegetative yields under extreme drought conditions of Jordan. The costs of agricultural mechanization and hand labor are very important in the production of forage crops in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change indicated that the productivity of forage crops is highly variable in simulated extreme drought conditions of Jordan, where rainfall or irrigation amounts and distribution are highly variable. [13] reported that selection of specific drought-tolerant hybrid of silage corn seeds in Jordan would be an efficient and useful method of improving uniformity, water use efficiency, and providing superior seedling performance with the potential for improved vegetative yields under extreme drought conditions of Jordan. The costs of agricultural mechanization and hand labor are very important in the production of forage crops in Jordan.…”
Section: Discussionmentioning
confidence: 99%